Congenital giant cardiac tumor with severe left-ventricular inflow and outflow obstruction and arrhythmia treated with pulmonary artery banding and long-term amiodarone infusion - Daiji Takeuchi; Takeshi Hiramatsu; Toshio Nakanishi (Wolters Kluwer Medknow Publications, 2012)
We report a congenital giant cardiac tumor that occupied the majority of left ventricular cavity with severe left ventricular inflow and outflow obstruction. The hemodynamics were similar to univentricular physiology. He was treated with prostaglandins and bilateral pulmonary artery banding. He had frequent supraventricular tachycardia associated with ventricular pre-excitation that was controlled by long-term administration of intravenous amiodarone. The patient died due to sepsis after 3 months.